Implementación y aplicación del procedimiento de ultrasonido para control de calidad de la soldadura en tuberías de presión mediante la técnica difracción por tiempo de vuelo - Dávila Ortiz, Camilo Inty (2017)
In the present the Non Destructive Testing, are use as an instrument for control the quality of welding that are applicated in differents elements of industry, and this way are guarantee the good operation throught the time and avoid catastrophic failure that incite loss of resources. One of the most recognized Non Destructive Testing around the world is the Ultrasonic Testing, whose application depends of characteristics that be evaluate throught codes or specifications. Some of this techniques of Ultrasonic that uses for evaluate weld are: pulso-echo and time of flight diffraction techniques, each has advantages and limitations, however it has been determined that Time Of Flight Diffraction technique generate diffracted signals of defects instead of be reflected signals, this allow decrease cover discontinuity and increase the accurate sizing capability, always that the technique are applicated in plates with thicknesses higher of 13 mm until 300 mm. In accordance with ASME V code, appendix 3, the calibration blocks for piping are apliccable when have a diameter higher of 500 mm or 20 inches, wich means that Time Of Flight Diffraction technique can’t be apliccated in pipping under ASME V code.